A review of Billaea Robineau-Desvoidy of the eastern Palearctic and Oriental regions (Diptera: Tachinidae) - Zhang, Chun-Tian; Shima, Hiroshi; Wang, Qiang; Tschorsnig, Hans-Peter (Zootaxa, 2015)
The species of Billaea Robineau-Desvoidy (Diptera, Tachinidae) from the eastern Palearctic and Oriental regions are revised. Ten described species are recognized, viz. B. atkinsoni (Baranov) (new records for Japan, Laos, Malaysia, Pakistan and Thailand), B. ficorum (Townsend), B. fortis (Rondani), B. impigra Kolomiets (new record for China), B. kolomyetzi Mesnil, B. malayana Malloch, B. morosa Mesnil, B. robusta Malloch, B. steini (Brauer et Bergenstamm) and B. triangulifera (Zetterstedt) and nine species are described as new to science, B. brevicauda Zhang et Shima sp. nov. (China), B. carinata Zhang et Shima sp. nov. (China), B. chinensis Zhang et Shima sp. nov. (China and Vietnam), B. flava Zhang et Wang sp. nov. (China), B. kurahashii Zhang et Shima sp. nov. (Laos and Thailand), B. micronychia Zhang et Shima sp. nov. (China and Japan; previously misidentified from China as B. irrorata (Meigen)), B. papei Zhang et Shima sp. nov. (Malaysia), B. setigera Zhang et Shima sp. nov. (China) and B. verticalis Shima et Zhang sp. nov. (China). Billaea fasciata (Townsend, 1928) is treated as a junior synonym of B. ficorum (Townsend, 1916), syn. nov. Billaea irrorata is no longer recorded from the eastern Palearctic. A key to 19 species of Billaea from the eastern Palearctic and Oriental regions and 101 figures of male terminalia, bodies, heads and abdomens are given.